Community Empowerment Through the Formation of Nutrition Awareness Groups Among Adolescents as a Prevention of Stunting - Pratami, Evi; Nugrahini, Evi Yunita; Kasiati; Titi Maharrani; Sukesi (Frontiers in Community Service and Empowerment, 2024)
Stunting is a serious problem in the health and social that has a big impact. Curative efforts for stunting require high levels of material and non-material support, so that prevention becomes an effective and efficient step. This service involves empowering teenagers through the formation of nutrition awareness groups. The methods used are training, mentoring and evaluation, activities are carried out by examining participants health, providing material, practice and evaluation. This service was 37 participants, Wonoayu Health Center, Sidoarjo Regency. The result of the activity was the formation of a youth group regarding adolescent nutritional awareness, the results of the pretest knowledge about reproductive health were highest in the sufficient category (40.54%) and in the posttest there was an increase to the highest frequency in the good category (67.56%). The results of the pretest knowledge about stunting were highest in the poor category (51.35%) and in the posttest there was an increase to the highest frequency in the good category (62.16%) and in the pretest, knowledge about the role of adolescent nutrition as an effort to prevent stunting was highest in the poor category (54.05%,) and in the posttest, there was an increase to the highest frequency. good category (72.22%). In conclusion, this activity is able to increase teenagers' knowledge about reproductive health, stunting and the role of nutrition during adolescence in preventing stunting. Suggestions for activities continue to be carried out on an ongoing basis with the support of policy makers, schools and health service agencies.